The Regulation of CD4+ T Cell Responses during Protozoan Infections - Engwerda, Christian R.; Ng, Susanna S.; Bunn, Patrick T. (Frontiers in Immunology, 2014)
CD4+ T cells are critical for defense against protozoan parasites. Intracellular protozoan parasite infections generally require the development of a Th1 cell response, characterized by the production of IFNγ and TNF that are critical for the generation of microbicidal molecules by phagocytes, as well as the expression of cytokines and cell surface molecules needed to generate cytolytic CD8+ T cells that can recognize and kill infected host cells. Over the past 25 years, much has been learnt about the molecular and cellular components necessary for the generation of Th1 cell responses, and it has become clear that these responses need to be tightly controlled to prevent disease. However, our understanding of the immunoregulatory mechanisms activated during infection is still not complete. Furthermore, it is apparent that although these mechanisms are critical to prevent inflammation, they can also promote parasite persistence and development of disease. Here, we review how CD4+ T cells are controlled during protozoan infections and how these regulatory mechanisms can influence parasite growth and disease outcome.